Requirements-Based Visualization Tools for Software Maintenance and Evolution. - Buckley, Jim (Computer (00189162), 2009)
The article discusses the use of software visualization tools. Although an extensive body of research into software visualization exists, relatively few commercial software-maintenance packages incorporate the technology. Suspected reasons include a general lack of knowledge among programmers of visualization tools, and interoperability issues between the tools and common development environments. In addition, the development of visualization tools seldom is subject to a requirements-acquisition regimen.